PENERAPAN ASAS ULTIMUM REMIDIUM DALAM PENEGAKAN HUKUM TINDAK PIDANA UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Hisbul Luthfi (Fakultas Hukum Universitas Islam Malang, 2021)
The application of criminal law that was originally as an effort / last way (Ultimum Remedium)became the first effort/way (Primum Remedium)especially in applying Law No. 11 of 2008 as amended by Law No. 19 of 2016 on Information and Electronic Transactions (UUITE) In this research using a type of normative legal research using statue approach, conceptual approach, and case approach. This study aims to find out how the application of ultimum remedial principle in the study of criminal law, How to reconstruct the criminal policy of the use of Law No. 11 of 2008 on amendments to Law No. 19 of 2016 on ITE. Surely this requires the existence of over criminalization on the application of criminalization that ensures the existence of disharmony in the application of criminal law, which negates the sense of humanity.